Mechanical Energy Dissipation in a Multifunctional Battery System. Issue 6 (2016) - Tsutsui, Waterloo; Nguyen, Trung; Liao, Hangjie; Parab, Niranjan; Kukreja, Jaspreet; Siegmund, Thomas; Chen, Wayne
ABSTRACT: In this paper, we report on a multifunctional battery assembly, which possesses a balanced combination of energy storage capability and resistance to electrical failure under mechanical impact loading. The Granular Battery Assembly (GBA) presented here exhibits a mechanical response that emerges from features of granular and cellular media. We demonstrate that for the specific GBA embodiment considered in the present study, the electrical reliability following a mechanical loading event is substantively increased compared to that of plain battery cells. The increased reliability is due to the sacrificial material elements interspersed between the battery units, attributing energy absorption and local stress limiting.